Answer:
7/4 +1/6 +X=15/2
1/6+X=15/2-7/4
1/6+X=30/4-7/4
X=23/4 - 1/6
X= 138-4/24
134/24
5.58333
Step-by-step explanation:
Well dont you have to bring down the zeros than you will have the answer
Answer:
Step-by-step explanation:
6/4=(6-1)/(4-x)
6/4=5/(4-x)
6(4-x)=4(5)
24-6x=20
-6x=-4
x=4/6
x=2/3
2/3 of an inch should be cut off the width.
Answer:
OPtion B
Step by step explanation:
Lets plug in a random value for x.
Lets say 5 is x
-8(-5-5)=(y+1)^2
5-5 = 0
-8(0) = 0
0 = (y+1)^2
Square root of both sides
0 = y+1
subtract one from both sides
-1 = y
that means the x is 5 and the y is -1. Option B illustrates exactly that!
Answer:
idk lol
Step-by-step explanation:
;p